Oxygenation and intestinal perfusion and its association with perturbations of the early life gut microbiota composition of children with congenital heart disease - Renk, Hanna; Schoppmeier, Ulrich; Müller, Jennifer; Kuger, Vanessa; Neunhoeffer, Felix; Gille, Christian; Peter, Silke (Frontiers in Microbiology, 2025)
BackgroundEarly life gut microbiota is known to shape the immune system and has a crucial role in immune homeostasis. Only little is known about composition and dynamics of the intestinal microbiota in infants with congenital heart disease (CHD) and potential influencing factors.MethodsWe evaluated the intestinal microbial composition of neonates with CHD (n = 13) compared to healthy controls (HC, n = 30). Fecal samples were analyzed by shotgun metagenomics. Different approaches of statistical modeling were applied to assess the impact of influencing factors on variation in species composition. Unsupervised hierarchical clustering of the microbial composition of neonates with CHD was used to detect associations of distinct clusters with intestinal tissue oxygenation and perfusion parameters, obtained by the “oxygen to see” (O2C) method.ResultsOverall, neonates with CHD showed an intestinal core microbiota dominated by the genera Enterococcus (27%) and Staphylococcus (20%). Furthermore, a lower abundance of the genera Bacteroides (8% vs. 14%), Parabacteroides (1% vs. 3%), Bifidobacterium (4% vs. 12%), and Escherichia (8% vs. 23%) was observed in CHD compared to HCs. CHD patients that were born by vaginal delivery showed a lower fraction of the genera Bacteroides (15% vs. 21%) and Bifidobacterium (7% vs. 22%) compared to HCs and in those born by cesarean section, these genera were not found at all. In infants with CHD, we found a significant impact of oxygen saturation (SpO2) on relative abundances of the intestinal core microbiota by multivariate analysis of variance (F[8,2] = 24.9, p = 0.04). Statistical modeling suggested a large proportional shift from a microbiota dominated by the genus Streptococcus (50%) in conditions with low SpO2 towards the genus Enterococcus (61%) in conditions with high SpO2. We identified three distinct compositional microbial clusters, corresponding neonates differed significantly in intestinal blood flow and global gut perfusion.ConclusionEarly life differences in gut microbiota of CHD neonates versus HCs are possibly linked to oxygen levels. Delivery method may affect microbiota stability. However, further studies are needed to assess the effect of potential interventions including probiotics or fecal transplants on early life microbiota perturbations in neonates with CHD.